Are We Still Needed? Reflections on the Profession in BIALL's Fiftieth Anniversary Year. (June 2019) - Speight, Dunstan
Abstract: In this article Dunstan Speight, President of BIALL 2018–2019, provides a short overview of current challenges and opportunities facing the profession. In addition to trends affecting all types of law libraries, the article discusses some of the main issues facing the three main types of information service: academic, law firm and chambers, and professional bodies. The article concludes with a discussion of how core skills and experience are still relevant in the fast-changing world of legal information.